Inoculum Influenced Glycohydrolases Production in the endophytic fungus Annulohypoxylon stygium DR47 - de Luca, Rafaela Coimbra; Balen, Manuela; da Silva, André Felipe; Rabelo, Sarita Candido [UNESP]; Pimentel, Ida Chapaval; Robl, Diogo (FapUNIFESP (SciELO), 2025)
Fungal enzymes have potential applicability in plant biomass deconstruction, such as in sugarcane bagasse hydrolysis for biorefinery application. Due to biomass complexity it is necessary to use a set of enzymes in addition to cellulolytic enzymes extracts to hydrolyze the hemicellulose and cellulose efficiently, such as β-glucosidase and pectinases. In this way, this work aimed to study the influence of inoculum in pectinase and β-glucosidase production of Annulohypoxylon stygium DR47 and evaluated culture media components in enzymatic production. Initially, mycelia fragmentation and the carbon source were tested in enzymatic production. The best production occurred with a pre-inoculum, incubated for 48 h, with blender fragmented mycelia cultivated in fructose (20 g∙L-1), as carbon source. Subsequently, tests containing agro-industrial residues (20 g∙L-1) were done to determine the best source for β-glucosidase and pectinases production in the enzyme production medium. Citrus bagasse (CB) was the substrate that induces higher titration of both enzymes (2.36 Upectinase∙mL-1; 1.82 Uβ-glucosidase∙mL-1). In this way, Plackett & Burman experimental design was performed with CB (20 g∙L) as the only carbon source to determine the influence of media components in enzyme production. The pectinase production was negatively affected by ZnSO4 and positively affect by urea, (NH4)2SO4, and MnSO4. Besides significant differences in β-glucosidase production were observed, with a positive effect on urea and peptone addition. In this way, further studies considering C/N ratios and consequently different nitrogen concentrations should be done to better understand the fungus physiology.
Keywords: Annulohypoxylon stygium; endophytic fungus; Glycohydrolases; pectinase; β-glucosidase